Geographical variation and correlates of substance use among married men in Ethiopia: spatial and multilevel analysis from Ethiopian Demographic and Health Survey 2016. Issue 9 (23rd September 2022) - Zenbaba, Demisu; Yassin, Ahmed; Abdulkadir, Adem; Mama, Mohammedaman
Abstract : Objective: The use of substances has become one of the world's most serious public health and socioeconomic issues. Most nations in sub-Saharan Africa, including Ethiopia, are undergoing significant economic transitions, creating a favourable environment for socially destructive substance use. This study aimed to determine the geographical variation, prevalence and correlates of substance use among ever-married men in Ethiopia. Design: A community-based cross-sectional survey was undertaken from 18 January 2016 to 27 June 2016. Data source: Data were used from the 2016 Ethiopian Demographic and Health Survey (EDHS). Data extraction and analysis: Data from the 2016 EDHS was used, and a total of 7793 ever-married men were involved in the analysis. The spatial autocorrelation statistic (Global Moran's I) was used to determine whether substance use was dispersed, clustered or randomly distributed. A multilevel logistic regression model was used to identify the correlates with substance use, and statistical significance was declared at p<0.05 and 95% CI. Results: Of all ever-married men, 72.5% (95% CI 71.5% to 73.4%) were currently using at least one of the three substances (alcohol, cigarettes and chat). The highest hotspot areas of substance use were observed in Ahmara and Tigray regions. The age (adjusted OR, AOR 1.80; 95% CI 1.32 to 2.45), educational status (AOR 0.64; 95% CI 0.51 to 0.82), occupation (AOR 1.36; 95% CI 1.05 to 1.76), watching television (AOR 1.50; 95% CI 1.25 to 1.81) and living in the city (AOR 2.25; 95% CI to 1.36 to 3.74) were individual and community-level correlates found to have a statistically significant association with substance use. Conclusion: In this study, nearly three-fourths of married men used one of the three substances. Given these findings, it is critical to reducing the problem by improving modifiable individual-level variables such as educational status and reducing substance advertising.